Episiotomy in Low-Risk Deliveries: Physician Factors - Arroll, Bruce (1990)
From 376 randomly selected nulliparous women who delivered at the Grace Hospital in 1986, we selected 133 low-risk women and performed a retrospective chart review to ascertain the episiotomy rate for physicians by sex, years since graduation, and specialty status. There was a statistically significant difference between the rate for specialists (65%) and general practitioners (38%). A non-significant difference was found between male physicians (41%) and female physicians (56%) and between physicians who had graduated within 15 years (42%) and those who graduated more than 15 years ago (52%). Subgroup analysis of the general practitioner data revealed different patterns for male and female physicians according to their graduation cohort.